Analisis Tentang Konsep Mekanisme Pasar Dan Moneter Menurut Pandangan Ibnu Taimiyah - Hakim, Luqman; Nuraeni; Suleman, Dede (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2025)
This study adopts a literature review approach to explore the concept of Islamic economics, with a particular emphasis on market and monetary mechanisms. The discussion draws on Islamic economic literature and the insights of scholars who possess a profound understanding of Shari’a law and its application within economic systems. The focus is directed toward the ideas of Ibn Taymiyyah, serving as the central subject of analysis. The findings indicate that the fundamental distinction lies in the underlying paradigm and principles shaping the formulation of theories and the implementation of market and monetary practices. Ibn Taymiyyah’s perspective, founded on the principle of Tawheed and applied as an act of worship to Allah SWT, leads to mechanisms that prioritize public benefit (maslahah) and uphold justice.